Evaluation of Phytochemical, Antioxidant, and Memory-Enhancing Activity of Garuga pinnata Roxb. Bark and Bryophyllum pinnatum (Lam) Oken. Leaves - Ravin Bhandari; Sabina Gyawali; Nisha Aryal; Devika Gaire; Kalpana Paudyal; Abaru Panta; Pooja Panth; Dirgha Raj Joshi; Rabindra Kumar Rokaya; Pramod Aryal; Jitendra Pandey (The Scientific World Journal)
Garugapinnata Roxb. (Burseraceae) is a medium-sized tree widely available all over the tropical regions of Asia. Bryophyllum pinnatum (Lam) Oken. (Crassulaceae) is an indigenous and exotic plant grown in tropical regions. Both plants have been used for their anti-inflammatory, antioxidant, anticancer, wound healing, antidiabetic activities, etc. This investigation was designed to explore the result shown by methanolic extract of Garuga pinnata bark and Bryophyllum pinnatum leaves, on cognitive power and retention of the memory in experimental mice along with quantification of phenolic compounds and DPPH radicals neutralizing capacity. The memory-enhancing activity was determined by the elevated plus-maze method in Scopolamine-induced amnesic mice, using Piracetam as allopathic and Shankhpushpi as ayurvedic standard drugs. Two doses (200 and 400 mg/kg p.o.) of both extracts were administered to mice up to 8 consecutive days; transfer latency of individual group was recorded after 45 minutes and memory of the experienced things was examined after 1 day. DPPH assay method and the Folin–Ciocalteu method were employed to determine antioxidant potency and total phenol amount, respectively. 400 mg/kg of the methanolic B. pinnatum bark extract significantly improved memory and learning of mice with transfer latency (TL) of 32.75 s, which is comparable to that of standard Piracetam (21.78 s) and Shankhpushpi (27.83 s). Greater phenolic content was quantified in B. pinnatum bark extract (156.80 ± 0.33 µg GAE/mg dry extract) as well as the antioxidant potency (69.77% of free radical inhibition at the 100 µg/mL concentration). Our study proclaimed the scientific evidence for the memory-boosting effect of both plants.